Analisis Tingkat Kebugaran Jasmani Dan Keterampilan Dribbling Passing Ekstrakurikuler Bola Basket SMAN 5 Malang: An Analysis of Physical Fitness Levels and Dribbling and Passing Skills among Basketball Extracurricular Students at SMAN 5 Malang - Mochammad Ali Topan; Siti Nurrochmah (Universitas Hamzanwadi, 2026)
Physical fitness and basic technical skills are important factors that support the performance of basketball players. However, based on initial observations at SMA Negeri 5 Malang, no measurements of physical fitness and basic technical skills have been conducted on members of the basketball extracurricular club. This study aims to analyze the level of physical fitness, dribbling and passing skills. The method used is quantitative descriptive with a survey design. The research sample consisted of 55 students selected using purposive proportional sampling. The research instruments were Indonesian physical fitness tests and basketball passing and dribbling skill tests that had been tested for validity and reliability. The data were analyzed using descriptive statistics and Pearson's Product Moment correlation. The results showed that the students' physical fitness levels were dominated by the very poor 49.09% and poor 45.45% categories. Passing skills were in the good category 92.73%, while dribbling skills were dominated by the poor category 41.82%. Correlation analysis showed a significant relationship between speed, arm muscle strength, leg muscle power, and cardiovascular endurance with dribbling skills p < 0.05. The conclusion of this study is that physical fitness and dribbling skills are still low, so a structured training program that integrates physical development and skills is needed.